The adolescent towards knowledge - Compagnucci, Elsa Rosa (2002)
The following article deals with knowledge, relationships, representations and values that pupils together with teachers perform daily at school. It includes our research project called “Adolescence and School” which has been implemented since 1995 in our Institution, subject called “Psychological Foundation on education”. Throughout its development, we have tried to get to know about in what positions teachers and students are towards knowledge. Our purpose is to make a critic- reflexive perspective possible on the part of university students who are to become teachers, as regards their knowledge on how students are formed on the E.G.B and Polimodal school levels. (1) What plays one of the main roles on the student’s career choice is their getting closer to the educative institution as well as to their teachers and the culture of the school. We have chosen a qualitative perspective for this article. Our proceedings on the working field are focused on teacher’s interviews and on the participation of two or three students that had access to the concretion of a semi-structured interview. A central topic within teacher’s and student’s speeches were the topics dealt in class and their motivation, been there a convergence with respect to the effects that these factors have over learning. Therefore, there is no reflection by the actors as regards the role that intention and willingness play in teacher-student-knowledge relationship and its projection in the teachinglearning process.